2015
DOI: 10.1016/j.actamat.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the degradation of BaTiO3 resistivity due to hydrogen ion incorporation: Impedance spectroscopy and diffusion analysis

Abstract: a b s t r a c tThe resistivity of insulator oxide materials can be compromised when they are exposed to hydrogen gas at high temperatures, as insulation resistance can significantly decrease. In this study, we differentiate between electrode, grain boundary, and grain contributions to total resistivity by impedance spectroscopy (IS) tests and a 3RC model. It turns out that the largest contribution to total resistivity comes from electrode Schottky barriers, which control the major part of the degradation. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…It has been shown that Cole-Cole plots of BME BaTiO 3 capacitors can be best tted by 3RC model. 7,10,46 Since the electrode has the largest loss of resistance due to hydrogen exposer among the other RC's (grains and grain boundaries), 7 it would be more sensitive to proton concentration. Therefore, the electrode conductance was extracted from the Cole-Cole plots and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Cole-Cole plots of BME BaTiO 3 capacitors can be best tted by 3RC model. 7,10,46 Since the electrode has the largest loss of resistance due to hydrogen exposer among the other RC's (grains and grain boundaries), 7 it would be more sensitive to proton concentration. Therefore, the electrode conductance was extracted from the Cole-Cole plots and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] The resistivity degradation of multilayer BaTiO 3 dielectrics structure has been studied by a number of other reports. 7,8 In contrast to those oxygen vacancy controlled time dependent break down processes, [9][10][11] the effects of H + has been rarely considered. In our recent investigations of the effects of H + , it was demonstrated that there are major changes that signicantly reduce the electrode Schottky barrier width, especially at the electrode interfaces, as determined by combined in situ impedance spectroscopy and I-V analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…115 The resistance of grains and grain boundaries under different 116 hydrogen gas exposure times is shown in Figure 1 facial grain boundary resistance [11]. 124 The change in GB resistance can be used to determine the diffu-125 sion of hydrogen into the grain boundaries, by defining appropriate 126 boundary conditions and solving Fick's law, one can estimate diffu-127 sion coefficient of protons at 135°C in grain boundaries [21]. One observation is that the critical temperature is 140°C for the 168 uncoated varistor, and it can increase to 250°C by applying 169 10 nm of HfO 2 ALD coating.…”
mentioning
confidence: 99%
“…In addition, to obtain an atmosphere with an oxygen partial pressure in order of 10 -10 atm, hydrogen gas should be used as a reducing agent. It was demonstrated that hydrogen can diffuse into electroceramic devices and degrade their insulation properties [9][10][11][12] . In order to avoid these shortcomings, one solution is to sinter the devices in less reducing atmosphere, e.g.…”
Section: Introductionmentioning
confidence: 99%